Depth Measurement Method Using Mono Image Processing Aided With Laser Pointer - AKHSANI (NIM 13102103); Pembimbing: Prof. Dr. Ir. Muljowidodo, FAQIH
In machine vision technology development, image processing has been desired to be able to produce data of depth, from system to the inspected object. The most popular method to achieve that aim is by using stereo image processing. However, in practice, the method is still hard to be applied in live mode. This final project tries to give an alternative method by using mono image processing aided by laser pointer. In order to achieve mentioned idea, an image processing system which produces depth output in live mode has been made. Depth outputs from the system then compared with depth outputs from a depth measurement device, which is a laser distance sensor. The laser distance sensor is also act as a laser pointer. Therefore it could be certain that the system and the comparing measurement device are pointing to a same point. The produced system has been able to measure depth in live mode by several conditional limitations. However, the system still has a large amount of standard deviation, thus it not quite consistent in measuring depth. This research hopefully could be used as reference for machine vision system productions which measure depth by similar method in upcoming future.